Innovative Applications of Natural Language Processing and Digital Media in Theatre and Performing Arts (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
The objective of our research is to investigate new digital techniques and tools, offering the audience innovative, attractive, enhanced and accessible experiences. The project focuses on performing arts, particularly theatre, aiming at designing, implementing, experimenting and evaluating technologies and tools that expand the semiotic code of a performance by offering new opportunities and aesthetic means in stage art and by introducing parallel accessible narrative flows. In our novel paradigm, modern technologies emphasize the stage elements providing a multilevel, intense and immersive theatrical experience. Moreover, lighting, video projections, audio clips and digital characters are incorporated, bringing unique aesthetic features. We also attempt to remove sensory and language barriers faced by some audiences. Accessibility features consist of subtitles, sign language and audio description. The project emphasises on natural language processing technologies, embedded communication and multimodal interaction to monitor automatically the time flow of a performance. Based on this, pre-designed and directed stage elements are being mapped to appropriate parts of the script and activated automatically by using the virtual "world" and appropriate sensors, while accessibility flows are dynamically synchronized with the stage action. The tools above are currently adapted within two experimental theatrical plays for validation purposes.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.